Edukasi Pencegahan dan Penyebaran Covid-19 di Wilayah Danau Kelurahan Harapan Baru Bekasi Utara - Navanti, Dovina; Joyosemito, Ibnu Susanto; Shanti, Sophia; Kartika, Wahyu; Hasaya, Haudi (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2021)
Public awareness of the COVID-19 pandemic is very lacking, many people ignore Covid- 19. Based on the latest data from the pikokabsi.bekasikab.go.id page, positive confirmed cases of Covid-19 in 2021 reached a total of 20,224 cases. Thus, it is necessary to make efforts to increase public awareness about preventing family-based Covid-19 transmission to help raise public awareness in Bekasi. With the number of positive patients exposed to this virus which is increasing, the community does not stop worrying and there are new policies from the government. There are so many factors that cause the continued increase in Covid-19 patients, one of which is public awareness about Covid-19, making the government easily identify cases. In this case, the program that we have carried out is to provide understanding to residents both in the Duta Harapan Bekasi Housing and the surrounding community regarding the prevention and spread of Covid- 19. Seeing from the potential of people who ignore the government's appeal that we are required to work, study and worship at home for a while to prevent the transmission of Covid-19. We have conducted an education program for the community in Duta Housing Lake, Harapan Baru Village, North Bekasi, Bekasi City. From the results of the interview, it can be seen that the community does not fully understand about Covid-19. So the solution we are doing is to provide education directly to the public by distributing masks, providing hand sanitizers and spraying disinfectant liquid to public facilities, the aim is also to provide an understanding to the wider community about Covid-19 and its prevention standards according to the government in the hope of bringing changes in the form of potential improvements. public understanding of Covid-19.